Harnessing precision population health tools to advance primary health care - Wanjuki, Ndirangu (Primary Health Care Practice Journal, 2025)
Abstract The 2023 Universal Health Coverage (UHC) Global Monitoring Report emphasizes the urgent need to reorient health systems toward a primary health care (PHC) approach to help accelerate progress toward the 2030 UHC targets. This article outlines precision population health as a strategic pathway for this shift. It delike ecosystem-wide diagnosis and coaching foster collaborative problem-solving. Lean models, including last mile services, self-care, and virtual learning, enhance access to health services and efficiency .A subsequent publication will examine the remaining three domains. Development agencies and philanthropic organisations are urged to prioritise technical assistance that emphasises skills development and fosters South-South learning and collaboration to support government-led scaling of precision population health tools towards UHC and system resilience.
©dirangu Wanjuki et al. Primary Health Care Practice Journal. This is an Open Access article distributed under the terms of the Creative Commons Attribution International 4.0 License (https://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited. Cite this article: Ndirangu Wanjuki et al. Harnessing precision population health tools to advance primary health care. Primary Health Care Practice Journal. 2025;1:2. [doi: 10.11604/PHCP.2025.1.2.46265]
Keywords: Precision population health; universal health coverage; health equity; Data science; health system efficiency